BECOMING AN ENTERPRISE DJANGO DEVELOPER discover best practices, tooling, and solutions for writing and organizing Django applications in production - Dinder, Michael (PACKT PUBLISHING LIMITED, 2022)
A Python web developer's guide to exploring the Django development lifecycle - beyond the basics Key Features Expert tips to help you use the right packages, tools, and libraries and understand their scope for your project Gain a thorough understanding of the essential components that comprise a large-scale Python web app Learn best practices for creating a project structure for better performance Book Description Django is a powerful framework but choosing the right add-ons that match the scale and scope of your enterprise projects can be tricky. This book will help you explore the multifarious options available for enterprise Django development. Countless organizations are already using Django and more migrating to it, unleashing the power of Python with many different packages and dependencies, including AI technologies. This practical guide will help you understand practices, blueprints, and design decisions to put Django to work the way you want it to. You'll learn various ways in which data can be rendered onto a page and discover the power of Django for large-scale production applications. Starting with the basics of getting an enterprise project up and running, you'll get to grips with maintaining the project throughout its lifecycle while learning what the Django application lifecycle is. By the end of this book, you'll have learned how to build and deploy a Django project to the web and implement various components into the site. What you will learn Use Django to develop enterprise-level apps to help scale your business Understand the steps and tools used to scale up a proof-of-concept project to production without going too deep into specific technologies Explore core Django components and how to use them in different ways to suit your app's needs Find out how Django allows you to build RESTful APIs Extract, parse, and migrate data from an old database system to a new system with Django and Python Write and run a test using the built-in testing tools in Django Who this book is for This book is for Django developers who want to learn the full-stack enterprise app development lifecycle. If you are a Python web developer looking to learn how to maintain a production website and explore Django beyond the basics, this book is for you. The book assumes intermediate-level knowledge of Python programming and the Django framework.